Nutritional Significance and Antioxidant-Mediated Antiaging Effects of Finger Millet: Molecular Insights and Prospects - Kumar, Anil; Rani, Madhu; Mani, Shalini; Shah, Pallavi; Singh, Dev Bukhsh; Kudapa, Himabindu; Varshney, Rajeev K. (Frontiers in Sustainable Food Systems, 2021)
Ageing is a multifaceted process which is associated with progressive, lethal and unalterable changes like damage to different molecules (DNA, proteins and lipids), cells, tissues and organs. It is an inevitable process but can be delayed by both genetic and dietary interventions. Besides ageing, premature death and age-associated diseases can be dealt with diet regulation and use of compounds which inhibit the stress responsiveness or promote the damage repair signaling pathways. Natural compounds offer a repertoire of highly diverse structural scaffolds that can offer hopeful candidate chemical entities with anti-ageing potential. One such source of natural compounds are millets which are minor cereals with abundance of high fiber, methionine, calcium, iron, polyphenols and secondary metabolites, responsible for numerous potential health benefits. The present review article elucidates the nature and significance of different phytochemicals derived from millets with a major focus on finger millet and highlights all the important studies supporting their health benefits with special emphasis on the anti-ageing effect of these compounds. The present article also proposes the possible mechanisms through which millets can play significant role in suppression of ageing processes and ageing related diseases by influencing genetic repair, protein glycation and stress responsive pathways. We further discuss well-established natural compounds for their use as anti-ageing drugs and recommend raising awareness for designing novel formulations/combinations from them so that their maximum anti-ageing potential can be harnessed for the benefit of mankind.